2022
DOI: 10.32322/jhsm.1110150
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of low-dose acetylsalicylic acid use and relation with inflammatory and thrombotic parameters on radial artery occlusion in patients undergoing elective transradial coronary angiography

Abstract: Aim: Transradial angiography (TRA) is recommended in clinical practice; it is better than the transfemoral route to prevent site-related complications. Radial artery occlusion is one of the most seen significant complications after TRA. In the present study, the protective effect of low dose acetylsalicylic acid (ASA) use against the radial artery occlusion (RAO) and the predictive ability of some thrombotic and inflammatory factors for the development of RAO were investigated. Material and Method: One t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, fibrinogen may impact endothelial damage, fibrin clot formation, thrombosis, abnormal blood flow, and platelet hyperactivity. As a degradation product of fibrinogen, D-dimer reflects thrombus formation and breakdown and has been identified as an independent risk factor for radial artery occlusion [ 40 , 41 ]. Our study demonstrated that fibrinogen is an independent risk factor for amputation in patients with ACS and deserves more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fibrinogen may impact endothelial damage, fibrin clot formation, thrombosis, abnormal blood flow, and platelet hyperactivity. As a degradation product of fibrinogen, D-dimer reflects thrombus formation and breakdown and has been identified as an independent risk factor for radial artery occlusion [ 40 , 41 ]. Our study demonstrated that fibrinogen is an independent risk factor for amputation in patients with ACS and deserves more attention.…”
Section: Discussionmentioning
confidence: 99%